A doxa‐informed practice analysis: reflexivity and representations, technology and action. (20th January 2015) - Ellway, Benjamin P. W.; Walsham, Geoff
Abstract The information systems (IS) work practice literature recognises that the use of information technology in organisations and broader social structuring is composed of both human action and the properties of technology. Social representations of work are important as reflexive agents may see contradictions between these and their use of technology in practice, thus providing a trigger for change. However, agents do not always see contradictions, which allows them to endure by favouring practice reproduction. To explain this inconsistency, this paper introduces the concept of doxa as a sensitising device for a practice analysis of call centre work and examines the narratives developed by advisors to represent their call‐handling practices. The contributions of our doxa‐informed practice analysis to the literature on IS and work practices include the following: firstly, to indicate how a simultaneous presence and absence of agents' reflexivity occurs; secondly, to demonstrate how the sensemaking function provided by social representations of work and technology can be undermined; and finally to show how material conditions of work and organisation may remain hidden, despite being directly implicated in the logic of practice.